Placement of Competency Based Structural Officials in the Youth Sports and Tourism Service of Serang Regency, Banten Province - Ayu, Deva Hartika; Helwani (Formosa Journal of Sustainable Research, 2023)
Competence is one of the important considerations in terms of employee placement in a particular position or position. This is in accordance with the principle of 'the right man on the right place', which means "the right person in the right place". A position that occupies a srtuktural position must of course consider the competence of the relevant employee. This research is entitled "Placement of Competency-Based Structural Officials at the Department of Youth, Sports and Tourism of Serang Regency, Banten Province (DISPORAPAR)". This study aims to understand the implementation related to the placement of structural official positions in DISPORAPAR Serang Regency Banten Province. In addition, this research also aims to find out things that become obstacle factors and efforts that can be made to resolve these obstacles. The method used in this research is qualitative research, with descriptive methods and inductive approaches. And for the data collection process, observation, interview, and documentation techniques were used. Furthermore, for data analysis techniques, the author applies data reduction techniques, data presentation, and conclusion drawing. From the research that has been done, the results show that the structural officials in DISPORAPAR have not been placed on target